Pulmonary hypertension in HIV infection: a prospective echocardiographic study. Issue 9 (11th May 2015) - Schwarze‐Zander, C; Pabst, S; Hammerstingl, C; Ohlig, J; Wasmuth, JC; Boesecke, C; Stoffel‐Wagner, B; Carstensen, A; Nickenig, G; Strassburg, CP; Rockstroh, JK; Skowasch, D; et al.
<x xml:space="preserve">Abstract</x> Objectives While idiopathic pulmonary arterial hypertension (PAH) is a rare disease, it is seen more frequently in patients with HIV infection. The aim of this study was to evaluate the prevalence of pulmonary hypertension (PH) in patients with HIV infection by echocardiographic screening. Methods Echocardiography and N‐terminal of the prohormone brain natriuretic peptide measurement were used to examine the prevalence of PH prospectively in HIV‐positive patients (n = 374) during routine follow‐up visits for HIV disease. Results In echocardiographic screening, PH was detected in a total of 23 of 374 HIV‐infected patients (6.1%). Of these, three patients (13%) presented with symptoms of dyspnoea and fatigue, and diagnosis of PAH was confirmed by right heart catheterization. Patients with systolic pulmonary artery pressure (sPAP) > 30 mmHg were more likely to be female, to have a history of injecting drug use and to originate from high‐prevalence countries (HPCs). Conclusions Echocardiographic screening detected PH in a substantial proportion of HIV‐positive patients. Female gender, a history of injecting drug use and HPC origin were associated with a higher prevalence of HIV‐associated PH. The relevance and long‐term outcome of these findings need to be validated in follow‐up studies, which are ongoing.